Fatal pulmonary embolism in hospitalised patients: a necropsy review. Issue 12 (24th November 2004) - Alikhan, R; Peters, F; Wilmott, R; Cohen, A T
Abstract : Aims: To carry out a retrospective review of all postmortem reports during the period 1991 to 2000 at King's College Hospital, London, as an extension of a previous analysis performed for the period 1965 to 1990. Methods: The number of deaths resulting from necropsy confirmed fatal pulmonary embolism in hospitalised patients was determined, and a limited analysis of the clinical characteristics of those patients who died was performed. Results: During the 10 year period, 16 104 deaths occurred and 6833 (42.4%) necropsies were performed. The outcome measure, fatal pulmonary embolism, was recorded as cause of death in 265 cases (3.9% of all necropsies; 5.2% of adult cases). No deaths from pulmonary embolism occurred in patients under 18 years of age; 80.0% occurred in patients older than 60 years. Of the fatal emboli, 214 of 265 (80.8%) occurred in patients who had not undergone recent surgery. Of these patients, 110 (51.4%) had suffered an acute medical illness in the six weeks before death, most often an acute infectious episode (26 cases). Conclusions: Thromboembolic events remain a relatively common cause of death in hospitalised patients and appear to occur more frequently in non-surgical than in surgical patients.